Fluid flow analysis of a shark-inspired microstructure. (1st September 2014) - Martin, Samuel; Bhushan, Bharat
Abstract: The scales of fast-swimming sharks contain riblet structures with microgrooves, aligned in the direction of fluid flow, that result in water moving efficiently over the surface. In previous studies, these riblet structures have shown a drag reduction of up to 10 % when compared with a smooth, flat surface. These studies have suggested two prevalent drag-reduction mechanisms which involve the effect of vortices and turbulence fluctuations. To further explore relevant mechanisms and study the effect of riblet geometry and flow properties on drag, vortices and turbulence fluctuations, various shark-skin-inspired riblet structures were created using computational models in which velocity, viscosity, spacing, height and thickness parameters were independently modified. A relevant mechanism of drag reduction is discussed to relate riblet parameters and flow properties to drag change and vortex size. Modelling information will lead to a better understanding of riblets and allow for optimum drag-reducing designs for applications in marine, medical and industrial fields.